A comparative study on convective heat transfer in indoor applications - Camci, Muhammet; Karakoyun, Yakup; Acikgoz, Ozgen; Dalkilic, Ahmet Selim (ELSEVIER SCIENCE SA, 2021)
Analytical solutions may not always be applicable in the calculation of the turbulent flow convective heat transfer rate, unlike the radiative and the conductive ones. Therefore, experimental correlations on convective heat transfer coefficient have been developed in enclosures. Convective heat transfer in a cavity is classified as natural, forced, and mixed convection on the basis of the driving forces (buoyant or mechanical). In recent years, there has been an increasing interest in the mixed convection, particularly in cooled ceiling-displacement ventilation indoor applications. It seems this interest is tending to increase while contamination of viruses and energy saving are growing as health and environmental concerns worldwide. Hence, the reasons behind the interest in mixed convection applications have been investigated along the paper. This comparative study seeks to explain the progress of convective heat transfer at indoor applications by reviewing mostly experimental correlation studies in time. The mixed convection has not been widely studied experimentally in indoor applications in comparison to natural and forced convection. Therefore, this study is devoted to indicate this gap in the literature on this issue and it includes all convection types with a wide and up-to-date review, descriptions, explanations, and comparisons, as well. Moreover, almost all empirical correlations on the topic are given in tables in detail. It can be concluded that general correlations for mixed convection applications is needed. Correlations related to radiant floor cooling applications are nearly non-existent. Additionally, more experimental studies are required for various split air conditioner cases. These gaps in the literature are unveiled and comparison of applications with various convection types have been made as a first comparative study in the literature. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Convective heat transfer coefficient; Natural convection; Mixed convection; Forced convection; Room ventilation; DISPLACEMENT VENTILATION; TRANSFER COEFFICIENTS; MIXING VENTILATION; RADIANT FLOOR; AIR-QUALITY; ROOM; PERFORMANCES; SURFACES; SYSTEMS; Construction & Building Technology; Energy & Fuels; Engineering